2013
DOI: 10.1007/s11746-013-2237-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and Scale‐up of Aqueous Surfactant‐Assisted Extraction of Canola Oil for Use as Biodiesel Feedstock

Abstract: Aqueous surfactant‐assisted extraction (ASE) has been proposed as an alternative to n‐hexane for extraction of vegetable oil; however, the use of inexpensive surfactants such as sodium dodecyl sulfate (SDS) and the effect of ASE on the quality of biodiesel from the oil are not well understood. Therefore, the effects on total oil extraction efficiency of surfactant concentration, extraction time, oilseed to liquid ratio and other parameters were evaluated using ASE with ground canola and SDS in aqueous solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Campbell and Glatz [3] suggested that the unextracted oil in soybeans was trapped in the disrupted cellular matrix due to its large droplet size, while sodium dodecyl sulfate (SDS) could facilitate the breakup of large oil droplets by lowering the interfacial tension (IFT) and making the oil extraction possible. SDS was also applied for the extraction of canola oil, and the highest total oil yield was 80 % [11]. In addition to the use of conventional surfactant, a recently developed new class of surfactants known as extended-surfactants was also reported for the AEP oil extraction process [12].…”
Section: Introductionmentioning
confidence: 99%
“…Campbell and Glatz [3] suggested that the unextracted oil in soybeans was trapped in the disrupted cellular matrix due to its large droplet size, while sodium dodecyl sulfate (SDS) could facilitate the breakup of large oil droplets by lowering the interfacial tension (IFT) and making the oil extraction possible. SDS was also applied for the extraction of canola oil, and the highest total oil yield was 80 % [11]. In addition to the use of conventional surfactant, a recently developed new class of surfactants known as extended-surfactants was also reported for the AEP oil extraction process [12].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum extraction of the canola was also supported with the optimum extraction time needed which was 30 mins and above. This was due to the phenomenon of stable decrement of IFT readings observed after 30 mins of canola extraction from the previous study (Tuntiwiwattanapun et al, 2013). The IFT value is very important in promoting oil extraction whereby lower IFT value with low CMC will enhance oil liberation mechanism while using less surfactant, which is safer for the consumer as this, may avoid irritation and toxicity.…”
Section: Effect Of Surfactant Concentration On Interfacial Tension Anmentioning
confidence: 75%
“…Surfactants have been applied in aqueous extraction processing to improve vegetable oil recovery. Sodium dodecyl sulfate was used to improve recovery of soybean oil (Campbell and Glatz, 2009) and canola oil (Tuntiwiwattanapun et al, 2013) by extracting the oil trapped in disrupted cellular matrix. The extendedsurfactants, which is a recently developed new class of surfactants that works by significantly reducing the interfacial tension, extracted 93-95% of total oil from the insufficiently ground peanut and canola seeds (Do and Sabatini, 2010).…”
Section: Highlightsmentioning
confidence: 99%